Verificação de seções retangulares de concreto armado submetidas à flexão oblíqua composta em situação de incêndio - Alan Mercedo Morais Moreira (2013)
In heating process of a concrete structure there is an abrupt reduction of the mechanical properties of the raw materials of reinforced concrete, concrete and steel, when this structure is subjected to a fire. This dissertation presents a method according to ABNT NBR 15200:2012, able to assess whether a reinforced concrete rectangular cross-section resists to a compound flexure when it is subjected to fire on four sides during a time recommended by ABNT NBR 14432:2001 and denominated required time of fire resistance (TRRF). The temperature distribution in the cross-section is strictly calculated, considering all nonlinearities involved. It was possible to achieve this using "THERSYS - System simulation via finite element method of 3D temperature distribution in structures subjected to fire", a software developed by RIBEIRO (2004) inside the Department of Structural Engineering of Universidade Federal de Minas Gerais. Some electronic spreadsheets were also developed to calculate and draw interactive diagrams, taking a normal force "N" constant and resistant in section, (bending moment around the X axis "Mx") x (bending moment around the Y axis "My"). The procedure may be used for generating these interactive diagrams in room temperature, in fire situation for the (TRRF) times recommended by Brazilian Standard and in post-fire situation when the cross-section had been subjected to one of the TRRF, specified previously, of exposition to fire and after that it was cooled down back to 20ºC.